Radiotherapy Delivery in Deep Inspiration for Pediatric Patients—Final Results of the Phase II Feasibility Study TEDDI - Østergaard, Daniella Elisabet; Young Lundgaard, Anni; Rechner, Laura Ann; Dejanovic, Danijela; Krogh Rose, Hanne; Hansen, Jolanta; Vaalavirta, Leila; Mokka, Miia; Aznar, Marianne; Wehner, Peder Skov; Hjalgrim, Lisa Lyngsie; Maraldo, Maja Vestmø (Wiley, 2026)
Introduction
The TEDDI trial tested the feasibility and reproducibility of deep-inspiration breath-hold (DIBH) in pediatric patients referred for radiotherapy. This report presents final results, including patient-reported outcomes (PRO) and dosimetric comparison of DIBH and free-breathing (FB).
Patients and Methods
Pediatric patients able to perform three sequential breath-holds and potentially requiring thoracic or upper abdominal radiotherapy were recruited. DIBH training was during staging or planning computed tomography (CT) scanning, using external gating with an external marker and visual coaching. Each patient underwent planning CT in both DIBH and FB, generating two radiotherapy plans. DIBH was selected if it resulted in a lower overall dose to organs at risk. At two centers, patients evaluated their DIBH experience during training. Those treated in DIBH also completed three daily questions and extended questionnaires at the start, midpoint, and end of treatment, using yes/no and five-point Likert scales.
Results
Twenty-five patients (12 females/13 males, median age 15 years, range: 9–17 years) were enrolled across three centers. Eight received photon radiotherapy, five in DIBH. Of 13 eligible patients, 11 rated DIBH training, with 10 selecting “Really good” or “Good.” Patients treated in DIBH reported feeling safe and comfortable. Dosimetric analysis showed clear heart and lung dose reductions with DIBH. FB patients had similar doses across both plans.
Conclusion
The TEDDI trial demonstrated the feasibility and safety of DIBH in pediatric radiotherapy. High compliance with the procedure and favorable dosimetric outcomes support the use of DIBH to reduce long-term toxicity risks in this population.